Ginsenoside Rh2-B1 stimulates cell proliferation and IFN-γ production by activating the p38 MAPK and ERK-dependent signaling pathways in CTLL-2 cells. (February 2014) - Lv, Shuang; Yi, Peng-Fei; Shen, Hai-Qing; Zhang, Li-Yan; Dong, Hai-Bing; Wu, Shuai-Cheng; Xia, Fang; Guo, Xun; Wei, Xu-Bin; Fu, Ben-Dong
Abstract Context: Ginsenoside Rh2, an active component of ginseng, exhibits immunoregulatory and anti-inflammatory properties. Rh2-B1, a sulfated derivative, was prepared to enhance its water solubility. We studied the effect of Rh2-B1 on CTLL-2, a CD8+ cytotoxic T cell line that was known for protecting against viral infection. Objective: We aimed to investigate the effect of Rh2-B1 on interferon (IFN)-γ production and cell proliferation and its possible mechanism. Materials and methods: Enzyme-linked immunosorbent assay (ELISA) was employed to analyze the IFN-γ concentration of the whole blood and the supernatant of CTLL-2 cell culture. Cell proliferation assay was conducted using the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. Western blots were used to evaluate changes in signal transduction pathways in CTLL-2 cells. Results: Rh2-B1 was able to enhance IFN-γ production from whole blood culture of Balb/c mice. We then evaluated the effect of Rh2-B1 on a cytotoxic T cell line, CTLL-2 for cell proliferation, IFN-γ production and its molecular mechanism. Rh2-B1 promoted cell proliferation and IFN-γ production of CTLL-2 cells. It also induced activation of p38 mitogen-activated protein kinase (MAPK) and extracellular-signal-regulated kinases (ERK), but inhibited p56 Lck and transducer and activator of transcription 5 (STAT5) expression. The effect was blocked by the specific p38 MAPK inhibitor SB203580 and ERK inhibitor U0126. Conclusion: Rh2-B1 could stimulate cell proliferation and IFN-γ production by activating the p38 MAPK- and ERK-dependent signaling pathways in cytotoxic T cells. This may be a novel medicine for treatment of viral infections.